2004
DOI: 10.1001/archinte.164.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Patient Sex on Intensive Care Unit Survival

Abstract: In a mixed medical-surgical ICU, older women have a higher mortality rate than men. This difference is not apparent for patients staying longer in the ICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
38
3
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 48 publications
5
38
3
1
Order By: Relevance
“…Similar findings have been reported previously, 2,7,13 although some controversy remains. [14][15][16] The reasons women may have a higher mortality than men during a critical illness are poorly understood, and clinical studies [17][18][19] have shown that women have higher mortality rates than men do despite biological evidence of the protective effect of estrogens on both immune function and cardiovascular responses.…”
Section: Discussionsupporting
confidence: 90%
“…Similar findings have been reported previously, 2,7,13 although some controversy remains. [14][15][16] The reasons women may have a higher mortality than men during a critical illness are poorly understood, and clinical studies [17][18][19] have shown that women have higher mortality rates than men do despite biological evidence of the protective effect of estrogens on both immune function and cardiovascular responses.…”
Section: Discussionsupporting
confidence: 90%
“…This age-sex relation is consistent with findings from smaller studies. 4,23 In previous studies, sex-related differences in outcomes among critically ill patients receiving mechanical ventilation were attenuated after adjustment for severity of illness;…”
mentioning
confidence: 97%
“…[1][2][3][4][5][6] The relationship between gender and outcomes after critical injury in humans remains unclear despite multiple observational studies. [7][8][9][10][11][12][13][14][15][16][17][18][19][20] Most studies have been unable to detect a difference in overall survival, even when adequately powered. 7,8,10,[12][13][14][15]18 An important difference between humans and animal models with regards to sexual dimorphism is the unique mechanisms of estrogen biosynthesis during stress that is present in humans (and other primates).…”
mentioning
confidence: 99%